Assessment of Women participation in Agriculture in Vavuniya district, Sri Lanka - Tharani, Gopalakrishnan; Akther, Mohamed Sameem Roshan; Ananthini, Nanthakumaran (International Journal of Social Sciences and Management, 2016)
An attempt was made to assess the women contribution towards agriculture in Vavuniya district, Sri Lanka. 60 farm family households' women were randomly selected from rural and urban area of Kovilkulam AI region of Vavuniya district in Sri Lanka and the data were collected by constructed questionnaire. The objectives of this study are to identify the factors contributing women participation in agriculture, to identify the constraints faced by the women in participating agriculture and to evaluate the women participation in decision making activity in agriculture. Minitab 15 and MS excel were used for data analysis. The level of women participation in agricultural activities was found out using chi-square test and the factors contributing for women participation in agricultural activities were identified using multiple regression analysis in urban and rural areas separately (α=0.05). The results revealed that 90% of the rural women respondents and 50% of the urban respondents participated in the agricultural activities which is a significant difference. The mean values of women participation in agricultural activities in urban and rural areas were 77 hours and 836 hours per annum respectively. The multiple regression model for women participation in urban area found that the participation of women negatively correlated with status of employment, age and education level (p=0.000). In rural area, age and educational level were negatively influencing on women participation in agricultural activities (p=0.000). R-square values of fitted regression models were 72 % and 91% in urban and rural area respectively 72% and 91% variation in respective women participation were explained by these models. The obstacles for the women in participation in agricultural activities were reported as lack of knowledge and training in agriculture field, family burden, cultural and social barriers and physical constraints. 60% of women from rural areas and 90% of women from urban areas were involved in decision making especially in the selection of crops and varieties for planting and livestock rearing. Enhancing the awareness and the technical knowledge to the women in the field of agriculture would contribute to increase income from agriculture at household level, district level and finally at national level. Int. J. Soc. Sc. Manage. Vol. 3, Issue-3: 159-162